Opportunities for tourism recovery and development during and after COVID-19 : views of tourism scholars versus tourism practitioners - Čorak, Sanda (Array, 2020)
For many years, tourism scholars have been investigating tourism development issues and disseminating their research results through papers published in academic journals. Although there is evidence that their viewpoints are in discrepancy with the viewpoints of tourism practitioners, these inconsistencies were rarely investigated and juxtaposed. As the global health pandemic caused by COVID-19 stopped travel and tourism all over the world, it created time for both groups of tourism experts to reflect on the various opportunities and challenges that the tourism sector will face in the future. Using the qualitative research design, the authors had the chance to collect, analyse and discuss the views of tourism experts on the recovery phase and possible changes to tourism in Croatia. Data was obtained through semi structured interviews of tourism practitioners from public and private sectors, and through literary review of published opinion papers by international scholars. The aim of the research was focused on the comparison of their views on the short-term recovery of tourism, as well as the long-term possibilities to transform the sector towards a more sustainable and more inclusive sector that is able to utilize the regional competitive advantages in the best possible way. The research results revealed more similarities regarding the attitudes on the recovery during short-term period, as opposed to more dissimilarity on the long-term future of tourism in Croatia. According to the research results, the future of tourism would benefit from the experience and knowledge of both groups combined – practitioners and scholars.